Shifter handover: An effective communication tool in Intensive Care Units (Research, Society and Development, 2025)
Objective: To understand the factors that influence effective communication between nurses during shift handovers in the ICU, as well as to identify elements that hinder shift handovers between ICU nurses. Method: This is a cross-sectional, observational, descriptive study using quantitative methods carried out during the ICU handover from September to November 2024. The structured script was divided into two parts: facilitating factors and hindering factors. Of the eight hundred observations, 77.50% were punctual in their arrival/shift handover and 100% used the institution's official script to hand over the shift to the other professional. Clear and objective communication was observed in 61.25% of the eighty observations. 52.50% of the factors hindering the handover of the shift were parallel conversations during the handover, 100% were noises such as alarms and telephone calls, and 36.25% were interruptions due to alarms and infusion pumps and/or mechanical ventilators. Conclusion: This study provides information on shift handovers in the ICU, highlighting the need to strengthen strategies to improve shift handovers. Identifying the main factors that hinder handovers, as well as the facilitators, are ways of creating improvement strategies to ensure continuity of care.